Remarkable Response to Neoadjuvant Therapy with Methotrexate, Vinblastine, Adriamycin, and Cisplatin for Undifferentiated Bladder Carcinoma: A Case Report and Literature Review - Kenji Numahata; Senji Hoshi; Kiyotsugu Hoshi; Nobuhiro Yasuno; Maiko Kubo; Isoji Sasagawa; Shoichiro Ohta (Case Reports in Oncology, 2014)
We report a case of primary undifferentiated bladder carcinoma, which revealed a remarkable response to methotrexate, vinblastine, adriamycin, and cisplatin (MVAC) therapy. A 46-year-old Japanese woman presented at the hospital with the chief complaints of gross hematuria and pain during urination. Cystoscopy revealed a large smooth-surfaced tumor in the urinary bladder. The histopathological diagnosis was undifferentiated carcinoma. The patient then received 3 courses of MVAC over a 3-month period. Hydronephrosis disappeared after the first course, and the tumor shrank rapidly. After completion of the third MVAC course, radical cystectomy and ileal conduit surgery were performed. After 7 years, the patient has still had no recurrences or metastases. We retrospectively review the relative efficacy of the two popular chemotherapeutic regimens in the management of muscle-invasive bladder cancer in patients who had had radical cystectomy.